The effects of repeated under canopy burning operations in commercial Pine plantations in Mpumalanga, South Africa on fuel loads and stand productivity - Pickup, Christopher Dale (Stellenbosch : Stellenbosch University, 2021)
Thesis (MFor)--Stellenbosch University, 2021.